Prison, Where Is Thy Victory? A Black Panther Theology of Mass Incarceration - Sowers, Brian P. (Harvard theological review, 2020)
On 12 July 1969, Huey P. Newton, cofounder of the Black Panther Party, wrote “Prison, Where Is Thy Victory?,” a socialist critique of America’s penal system that focused on its inability to rehabilitate prisoners. Beyond its explicit rejection of American capitalism, his essay, with its very title, also invokes two passages from the Bible—Paul’s epistle to the Corinthians (1 Cor 15:55) and the book of the prophet Hosea (Hos 13:14) —although Newton never elaborates on their allusive force. Intertextually bound to Newton’s title, these biblical passages function as a type of guiding lens through which “full-knowing readers” can engage Newton’s treatment of mass incarceration. This essay provides such an intertextual reading of “Prison” vis-à-vis 1 Cor 15 and Hos 13, with particular attention to the ways Newton’s biblical models simultaneously enrich and complicate interpretations of “Prison.”